ANALISIS DAMPAK LIMBAH APD TERHADAP MANAJEMEN PENGELOLAAN LIMBAH PADAT MEDIS SELAMA PANDEMI COVID-19 DI RUMAH SAKIT PERMATA DEPOK TAHUN 2020 - Yuniar Agis Sapitri (2021)
In the PPI strategy in preventing the transmission of COVID-19, PPE is a fundamental thing that is required by Permata Depok Hospital for all patients, visitors, staff and health workers who are in the hospital, such as the use of masks, gloves and protective clothing. From this, the use of PPE, which is very intensified, will result in piles of waste, especially in hospitals. PPE itself is included in solid medical hazardous waste. The aim of this researcher was to see how the impact of PPE waste during the pandemic period on B3 Medical Waste Management at Permata Depok Hospital. This research uses descriptive qualitative research with a systems approach. The results of this study indicate the impact of PPE waste in the management of B3 medical waste management during the pandemic, namely affecting in terms of handling more waste before being transported and increasing operational costs in supporting the purchase of equipment in B3 waste management.